Hubungan Perilaku dengan Kejadian Penyakit Demam Berdarah Dengue di Wilayah Kerja Puskemas Bakunase Kota Kupang - Putra A. U. Retang; Johny A. R. Salmun; Agus Setyobudi (Universitas Nusa Cendana, 2021)
Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus and transmitted through mosquito bites. The Aedes aegypti mosquito is the main vector. However, other species such as Aedes albopictus can also be vector transmitters. Some of the factors that influence the occurrence of DHF include low immunity status of community groups and increased mosquito population density due to the large number of breeding places in the rainy season. Currently, DHF is still a common disease and is one of the main public health problems in Indonesia. The number of cases of dengue fever in East Nusa Tenggara (NTT) Province in 2015 was 665 cases, in 2016 as many as 1,213 cases, and in 2017 as many as 542 cases. This study aims to analyze the relationship between behavior and the incidence of dengue fever in the working area of ​​the Bakunase Health Center, Kupang City. This study was an analytic observational study with a case-control design. Data were collected in January-February 2020. The results of this study indicate that there is no significant relationship between knowledge and attitude with the incidence of DHF, while action has a significant relationship with the incidence of DHF. Community empowerment efforts related to preventive measures need to be prioritized so that the risk of DHF disease can be reduced.